The Pathogen Profile of a Honey Bee Queen Does Not Reflect That of Her Workers - Jessica L. Kevill; Katie Lee; Michael Goblirsch; Erin McDermott; David R. Tarpy; Marla Spivak; Declan C. Schroeder (Insects, 2020)
Throughout a honey bee queen’s lifetime, she is tended to by her worker daughters, who feed and groom her. Such interactions provide possible horizontal transmission routes for pathogens from the workers to the queen, and as such a queen’s pathogen profile may be representative of the workers within a colony. To explore this further, we investigated known honey bee pathogen co-occurrence, as well as pathogen transmission from workers to queens. Queens from 42 colonies were removed from their source hives and exchanged into a second, unrelated foster colony. Worker samples were taken from the source colony on the day of queen exchange and the queens were collected 24 days after introduction. All samples were screened for Nosema spp., Trypanosome spp., acute bee paralysis virus (ABPV), black queen cell virus (BQCV), chronic bee paralysis virus (CBPV), Israeli acute paralysis virus (IAPV), Lake Sinai virus (LSV), and deformed wing virus master variants (DWV-A, B, and C) using RT-qPCR. The data show that LSV, Nosema, and DWV-B were the most abundant pathogens in colonies. All workers (n = 42) were LSV-positive, 88% were Nosema-positive, whilst pathogen loads were low (<1 × 106 genome equivalents per pooled worker sample). All queens (n = 39) were negative for both LSV and Nosema. We found no evidence of DWV transmission occurring from worker to queen when comparing queens to foster colonies, despite DWV being present in both queens and workers. Honey bee pathogen presence and diversity in queens cannot be revealed from screening workers, nor were pathogens successfully transmitted to the queen.